Dynamic characteristics and safety criterion of deep rock mine opening under blast loading. (July 2019) - Xu, Jinhui; Kang, Yong; Wang, Xiaochuan; Feng, Gan; Wang, Zefeng
Abstract: The blasting vibration in deep mining affects the safety of the adjacent roadways. To estimate the stability of a deep rock mass opening during blasting excavation, the dynamic responses of the deep rock mass subjected to blast loading are investigated in this study. The relationships between the blasting vibration velocity and the frequency over time, horizontal distance, and depth are analyzed, and the stress distribution of the surrounding rock mass is depicted through field tests and numerical simulation. The failure mechanism of deep rock mass is thus revealed, and a new safety criterion regarding the blasting vibration of the deep rock mass is put forward. The results indicate that the vertical vibration velocity is higher than the horizontal vibration velocity and that the vertical tension of the seismic wave of the blast is larger than that of the shearing action in the near-blasting field, which contrasts that of the far field. Both the vibration velocity and frequency decrease with an increase in time, distance, and depth, and the range of influence of the blasting vibration in terms of depth is larger than that for the horizontal direction. Therefore, the deep rock mass is more vulnerable to damage than the shallow rock mass under blast loading. In addition, the surrounding rock stress tends to transfer from the arc foot on the blasting side to the straight wall on the rear side, and the shear stress is ahead of the tensile stress. It was verified through a case calculation that the new criterion has practical value and can be used as a guide for evaluating the blasting vibration effects of the deep rock mass.